2015 Social Accounting Matrix for Jordan - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
The new 2015 SAM for Jordan includes 56 sectors and 62 products. It also includes 13 factors of production, labor is disaggregated across rural and urban areas and into four education-based categories, capital is also disaggregated into four subcategories: crops, livestock, mining, and other; and land. Households were split according to per capita expenditure into five quintiles by rural and urban areas.